Saddlebags, City Streets and Cyberspace A History of Preaching in the Churches of Christ - Casey, Michael W. (Abilene Christian University Press, 1995)
This innovative book traces the history of preaching in the Stone-Campbell tradition, seeing how styles of rhetoric emerged and blended together. It traces the development of debaters, peacemakers, evangelists, and the influence of media on preaching (radio, television, and internet). "This book by Mike Casey is pioneering scholarship. . . Whether or not one agrees with Mike, I predict that any future studies on preaching in our movement will, of necessity, commence with this book." -Thomas Olbricht